REAL STOCK RETURNS, INFLATIONARY TRENDS AND REAL ACTIVITY: Evidence from Malaysia - Majid, M. Shabri Abdul (Gadjah Mada International Journal of Business, 2002)
This study explores the relationship between real stock returns and inflationary trends in the Malaysian economy. It attempts to test for the relationship between real stock return and inflation in light of Fisher hypothesis that asserts the independence of real stock return and inflation and Famaâs (1981) proxy effect framework which states that the negative real stock returns-inflation is indirectly explained by a negative real economic activity-inflation and a positive real stock returns-real economicactivity relationships. The finding shows that real stock returns are independent of inflationary trends in accordance with the Fisher hypothesis, which implies that the Malaysian stock market provides a good hedge against inflation. The Famaâs proxy hypothesis is then tested to check for the consistency of the relationships. The positive relationship between inflation and real economic activity and the positive relationship betweenreal stock returns and real economic activity that totally contradicts the Famaâs proxy hypothesis however are found, to some extent, be consistent with the explanation of conventional macroeconomic theories of the Philipâs curve.